Relationship Marketing dan Pemanfaatan Teknologi Informasi dalam Customer Relationship Management untuk Memenangkan Persaingan Bisnis - Idris Gautama S. (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
This writing shows tough competitiveness in business world, and explores Relationship Marketing (RM)and its contribution in Customer Relationship Management (CRM). CRM is needed in obtaining new customer,retaining and enhanching existing customer. This writing also shows higher cost in obtaining new customerrather than retaining existing customer, moreover this writing explains how CRM that empowered by RM withbuilt in information technology may help corporation in winning the competition in business.Keywords: Relationship management, Customer Relationship Management, competition.